Progettare nella città antica - Iuliano, Francesco; Maurea, Margherita (TeA / Teaching Architecture, 2023)
http://www.fedoabooks.unina.it/index.php/fedoapress/catalog/book/447#:~:text=The%20publication%20collects,meet%20future%20challenges.